The Protection of Consumer Rights of BPJS Health Patients in the Perspective of Civil Law - Triani Indah Pawening; Ady Purwoto; Desty Anggie Mustika (JURNAL MAHASISWA YUSTISI, 2026)
The National Health Insurance Program (JKN), administered by BPJS Health, aims to provide equitable access to healthcare services. However, in practice, various issues still arise, such as service refusal, delays in medical treatment, and discrimination against participants. This study aims to analyze the application of civil liability principles in the legal relationship between patients and healthcare providers, as well as to identify the forms of breach of contract (wanprestasi) that occur. The research method used is normative juridical with a literature study approach, including analysis of laws and regulations, legal doctrines, and case studies. The results show that although regulations exist to protect the rights of BPJS patients as consumers, the implementation remains weak, often resulting in rights violations that may lead to civil liability. This study concludes that strengthening legal protection through regulatory enforcement, enhanced supervision, and education for BPJS participants is urgently needed to ensure fair and accountable healthcare services.